Respuesta :
Answer:
y = 10
Step-by-step explanation:
Simplifying
2.8y + 6 + 0.2y = 5y + -14
Reorder the terms:
6 + 2.8y + 0.2y = 5y + -14
Combine like terms: 2.8y + 0.2y = 3y
6 + 3y = 5y + -14
Reorder the terms:
6 + 3y = -14 + 5y
Solving
6 + 3y = -14 + 5y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-5y' to each side of the equation.
6 + 3y + -5y = -14 + 5y + -5y
Combine like terms: 3y + -5y = -2y
6 + -2y = -14 + 5y + -5y
Combine like terms: 5y + -5y = 0
6 + -2y = -14 + 0
6 + -2y = -14
Add '-6' to each side of the equation.
6 + -6 + -2y = -14 + -6
Combine like terms: 6 + -6 = 0
0 + -2y = -14 + -6
-2y = -14 + -6
Combine like terms: -14 + -6 = -20
-2y = -20
Divide each side by '-2'.
y = 10
Simplifying
y = 10